Exploring the Usage of Decision Making Tools in Malaysia, Factors Affecting the Accuracy of Decision Making - Low, Chui Ling (2010)
This research is conducted to explore the roles of Decision Making Tools (DMT) and factors affecting the accuracy of decision making in Malaysia. Based on the literature review, DMT have effectively used in forecasting, analyzing and evaluating 200 sets questionnaire have been distributed to seven companies for the purpose to prove the objectives and the hypothesis of this study. Results revealed time pressure, information accessible, behavior of decision makers and DMT have influenced the accuracy of decision makers. Lastly, recommendations on the usage of DMT have also discussed in this research.